Strengthening lecturer competence with the job-embedded professional development (jepd) model: a solution for dealing with education in the era of 5.0 and the metaverse - Kurniawan, Shopyan Jepri; Situmorang, Dominikus David Biondi; Ifdil, Ifdil (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2022)
The purpose of this study is to provide references related to the model of lecturers' pedagogic competence development in higher education. Pedagogic competence is fundamental in education. This is because pedagogic competence is one of the important factors in teaching. Pedagogic competence relates to how a lecturer can provide teaching that is not monotonous, fun, creative and meaningful and uses various types of media, especially in the Era of 5.0 and the Metaverse.